2022
DOI: 10.3389/fimmu.2022.978203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, effectiveness, and safety of herpes zoster vaccine in the immunocompetent and immunocompromised subjects: A systematic review and network meta-analysis

Abstract: ObjectiveTo investigate the efficacy, effectiveness and safety of recombinant zoster vaccine (RZV) and zoster vaccine live (ZVL) in immunocompetent and immunocompromised subjects.MethodsData sources: PubMed, EMBASE, Cochrane Library, and Web of Science databases (up to Jan 2022) were searched to identify English articles. Search terms included randomized controlled trials (RCTs), observational studies, herpes zoster, RZV, ZVL. Study Selection: Only randomized controlled trials (RCTs) evaluating vaccine efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…NNV is frequently used to compare potential benefits of different vaccination strategies in literature, 53 and the lower NNV for RZV compared with ZVL is due to the higher initial vaccine efficacy and sustained protection conferred by RZV over the projected period. Furthermore, our findings are supported by Xia et al, 54 a recent systematic review and network meta-analysis of global data, which reported that RZV was statistically superior to no vaccination and ZVL in terms of vaccine effectiveness. In particular, Xia et al 54 also found that RZV provided 36% and 45% more protection than ZVL in RCTs and medical practice, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…NNV is frequently used to compare potential benefits of different vaccination strategies in literature, 53 and the lower NNV for RZV compared with ZVL is due to the higher initial vaccine efficacy and sustained protection conferred by RZV over the projected period. Furthermore, our findings are supported by Xia et al, 54 a recent systematic review and network meta-analysis of global data, which reported that RZV was statistically superior to no vaccination and ZVL in terms of vaccine effectiveness. In particular, Xia et al 54 also found that RZV provided 36% and 45% more protection than ZVL in RCTs and medical practice, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, our findings are supported by Xia et al, 54 a recent systematic review and network meta-analysis of global data, which reported that RZV was statistically superior to no vaccination and ZVL in terms of vaccine effectiveness. In particular, Xia et al 54 also found that RZV provided 36% and 45% more protection than ZVL in RCTs and medical practice, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…For vaccine-related parameters, model inputs of vaccine efficacy were based on data sources, 33 , 34 , 67 which align with the studies identified in a recent systematic review and meta-analysis assessing HZ vaccine efficacy in immunocompetent individuals. 84 …”
Section: Discussionmentioning
confidence: 99%
“…Varicella zoster virus is a serious health threat due to the importance of its consequences, especially considering post-herpetic neuropathy. It is currently targeted by a live attenuated vaccine and by a recombinant vaccine; their efficacy is reported to be 84% at best, with two administrations of the recombinant one in immunocompetent subjects, but it can be absent in immunocompromised individuals using the live attenuated one [ 148 ]. Moreover, the vaccine effectiveness in preventing infection symptoms is reported to be generally lower [ 149 ] and the prevention of post-herpetic neuralgia remains an unmet medical need.…”
Section: Relevant Clinical Trials On Mrna Vaccinesmentioning
confidence: 99%